THELLIER PALEOINTENSITY THEORY AND EXPERIMENTS FOR MULTIDOMAIN GRAINS - Xu S.; Dunlop D.J. (My University, 2004)
We extend theories of thermoremanent magnetization (TRM) and partial TRM (pTRM) in multidomain (MD) grains to model thermal demagnetization and pTRM acquisition steps in Thellier paleointensity determination. Because of the interleaving of zero-field and in-field heating-cooling steps to increasing temperatures the initial state for any step is complex, and theoretical modeling is more intricate than for pTRM production or thermal demagnetization separately. At low to moderate temperature T, TRM lost exceeds pTRM regained, causing convex down Arai plots sagging below the ideal single-domain (SD) line. At moderate to high T, pTRM acquisition outweighs TRM loss. As T approaches TCurie, pTRM gain exactly equals TRM loss, and the Arai plot becomes ideal. When pTRMs are produced perpendicular to the original TRM and measured directly rather than by differencing field-on and field-off results, there is less deviation from ideality at low to moderate T. Our theory agrees semiquantitatively with results for parallel and perpendicular pTRMs for large MD magnetites (135 mum). Smaller MD magnetites (6 and 20 mum) have less curved Arai plots, and the smallest magnetites (0.6 and 1 mum) have almost linear plots. Positive pTRM checks demonstrate that curved Arai plots of MD grains are reproducible, unlike curved plots for rocks that alter physicochemically in the Thellier experiment, while negative pTRM tail checks indicate undemagnetized pTRM residuals. Low-temperature demagnetization improves linearity only slightly. Practical applications of this work include using the predicted threshold T below which no net pTRM is produced in a parallel Thellier experiment to screen data used for paleointensity fits. Straight line fits through low- and medium-T points in Arai plots of MD (135 mum) grains overestimated the paleofield by as much as 100% and for small pseudo-single-domain (PSD) (0.6 and 1 mum) grains overestimated by about 25%. However, by using linear segments of medium- to high-T data with f values >=0.5 it may be possible to obtain reasonable paleointensity estimates even for larger PSD (6 and 20 mum) and MD grains. Middle- to high-T fits for 0.6 mum grains gave paleointensities within 4% of the correct value, utilizing essentially the entire data set (f > 0.9). Perpendicular data always gave superior linear fits. Orienting samples with their natural remanent magnetizations perpendicular to the laboratory field is therefore recommended for rocks containing PSD and MD grains. However, double heatings are preferable to single heatings because they allow pTRM tail checks to be carried out.
Keywords: paleointensity determination; Thellier method; multidomain grains